Spinel (Ni0.4Co0.4Mn0.2)3O4 nanoparticles as conversion-type anodes for Li- and Na-ion batteries. Issue 6 (15th April 2019) - Ren, Qing-Qing; Yu, Fu-Da; Zheng, Li-Li; Yin, Bo-Si; Wang, Zhen-Bo; Ke, Ke
Abstract: High-capacity electrode materials are needed for electrochemical energy storage. Spinel (Ni0.4 Co0.4 Mn0.2 )3 O4 nanoparticles have been prepared by simplified and efficient coprecipitation in combination with thermal decomposition. As conversion-type anodes for lithium ion batteries (LIBs), the materials exhibit high capacities of 779 mAh g −1 after 600 cycles at the optimal current density of 0.5 A g −1 . The enhanced cycling performance of (Ni0.4 Co0.4 Mn0.2 )3 O4 electrodes benefits from multiple metal species providing synergic effects in electrical processes, nanosize favorable for releasing stress and optimal rate lithiation for generating unique solid electrolyte interphase (SEI) with reactivation ability. And, the SEI layer is critical for the cycling properties. Optimal rate lithiation offers in designing long-lived electrodes. Additionally, the spinel materials are evaluated in sodium systems. The different capacity fading behaviors of the (Ni0.4 Co0.4 Mn0.2 )3 O4 electrodes between lithium and sodium ion cells are concerned.